“Tied to the Land”: Climate Change Activism Among U.S. Hunters and Fishers - Love-Nichols, Jessica (Frontiers in Communication, 2020)
This paper investigates climate change activism among sportsmen and sportswomen, or hunters and fishers—a politically conservative group with historically deep roots to environmental conservation. Recently members of this community have created an NGO that focuses solely on climate change action—Conservation Hawks—and several other long-standing organizations have begun to include climate communication and activism within their mission. This article draws on fieldwork conducted throughout the rural western U.S., including ethnographic interviews with sportsmen/sportswomen, participant observation in hunter education courses and conservation events, and publicly-available media produced by hunting-oriented conservation organizations. Using an ethnographic and discourse analytic approach, I find that three primary discursive practices are particularly important within hunting and fishing community—a performed closeness to wildlife and wild places, a privileging of experiential and embodied epistemologies, and a valorization of the past wilderness. In both interviews and sportsmen-oriented media, these discourses can be drawn on when creating doubt and climate skepticism. Increasingly, however, activist groups use the same rhetorical strategies to promote climate change action. I argue that such shared discursive practices can thus mobilize collective identities, challenge political polarization, and create new political subjectivities around climate change in the rural western United States. I also argue that these discursive practices shape the actions portrayed as reasonable responses to the climate crisis within this community. This analysis thus illuminates climate activism within an understudied group, showing the depth of the civic movement on climate change. It also specifically highlights the importance of shared discursive practices to both climate skepticism and climate activism among one politically-conservative group in the United States, rural white hunters and fishers.